Efficacy of electrolyzed water to inactivate foodborne pathogens on fresh-cut apples - Graça, Ana (2015)
Chlorine is the most common disinfectant used in the fresh-cut industry but nowadays environmental and health risks have led to the need to find new sanitizers. Electrolyzed water (EW) appears to be a promising alternative. In this work, disinfection efficacy of acidic (AEW) and neutral (NEW) electrolyzed water in fresh-cut apple slices inoculated with Escherichia coli, Listeria innocua or Salmonella choleraesuis was studied. Apple slices were inoculated with a 10(7) cfu/ml suspension of pathogens and treated with the sanitizer EW solutions, with 100 or 50 ppm of free chlorine solutions and with distilled water. Population reduction was determined 30 min after washings and untreated apple slices were used as control in all assays. AEW100 was the treatment with more effective bactericidal activity followed by NEW100 and AEW50. EW had higher or similar efficacy than chlorine treatments in all tested conditions.